A comparison of Vietnamese, Malaysian, Thai and Indonesian EQ-5D-5L value sets using a Vietnamese sample of HER2 positive breast cancer patients - Nhi, Vo Ngoc Yen; Nhi, Tran Thi Yen; Y, Nguyen Tran Nhu; Nga, Nguyen Thi To; Thuy, Nguyen Thi Thu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Background: Vietnamese value set was published in 2019, but so far there has been no assessment comparison of the Vietnamese value set with other value sets. Objectives: To compare the Vietnamese, Malaysian, Thai, Indonesian value sets and evaluate the appropriateness of the Vietnamese value set for Vietnamese people. Methods: A cross-sectional study was conducted on 338 HER2 positive breast cancer patients are treating at 6 hospitals in Vietnam. Data was collected by taking the entire sample from July to December in 2019. The EQ-5D-5L health states ratings were collected through interviews with patients and utility scores were calculated using the Vietnamese, Malaysian, Thai and Indonesian value sets. The difference in the mean values from 4 value sets was verified by the Wilcoxon signed rank test and the consistency between value sets was assessed by using intraclass correlation coefficients (ICCs). Spearman's test was used to evaluate the correlation between the patient's demographic characteristics with EQ-5D score (95% confidence interval). Results: The study was performed on 338 patients with the mean age of 53.870 ± 9.970 and weight of patients of 54.589 ± 7.698 kg. The Thai value set had the highest mean utility score (0.904 ± 0.142), followed by the Indonesian value set (0.881 ± 0.117), Malaysian value set (0.867 ± 0.143) and the Vietnamese value set had the smallest mean utility score (0.863 ± 0.142). There was a very high consistency between the value sets ( intraclass correlation coefficients > 0.900). The forecasting model of EQ-5D VAS utility score based on EQ-5D-5L utility score from the Vietnamese value set had the highest R square (R2 = 0.231). Conclusion: Vietnamese, Malaysian, Thai, Indonesian value sets have an overall high level of correlation and consistency, in which the correlation of Vietnamese and Malaysian value sets is highest. The Vietnamese value set is most suitable for the Vietnamese HER2-positive breast cancer patients, the Malaysian value set is the second-best option to be applied.